Bupleurum chinense Roots: a Bioactivity-Guided Approach toward Saponin-Type NF-κB Inhibitors - Liu, Xin; Latkolik, Simone; Atanasov, Atanas G.; Kunert, Olaf; Pferschy-Wenzig, Eva-Maria; Heiss, Elke H.; Malainer, Clemens; Schinkovitz, Andreas; Kollroser, Manfred; Dirsch, Verena M.; Bauer, Rudolf (Planta Medica, 2017)
The roots of Bupleurum chinense have a long history in traditional medicine to treat infectious diseases and inflammatory disorders. Two major compounds, saikosaponins A and D, were reported to exert potent anti-inflammatory activity by inhibiting NF-κB. In the present study, we isolated new saikosaponin analogues from the roots of B. chinese interfering with NF-κB activity in vitro. The methanol-soluble fraction of the dichloromethane extract of Radix Bupleuri was subjected to activity-guided isolation yielding 18 compounds, including triterpenoids and polyacetylenes. Their structures were determined by spectroscopic methods as saikogenin D (1), prosaikogenin D (2), saikosaponins B2 (3), W (4), B1 (5), Y (6), D (7), A (8), E (9), B4 (10), B3 (11), and T (12), saikodiyne A (13), D (14), E (15) and F (16), falcarindiol (17), and 1-linoleoyl-sn-glycero-3-phosphorylcholine (18). Among them, 4, 15, and 16 are new compounds, whereas 6, previously described as a semi-synthetic compound, is isolated from a natural source for the first time, and 13–17 are the first reports of polyacetylenes from this plant. Nine saponins/triterpenoids were tested for inhibition of NF-κB signaling in a cell-based NF-κB-dependent luciferase reporter gene model in vitro. Five of them (1, 2, 4, 6, and 8) showed strong (> 50%, at 30 µM) NF-κB inhibition, but also varying degrees of cytotoxicity, with compounds 1 and 4 (showing no significant cytotoxicity) presenting IC50 values of 14.0 µM and 14.1 µM in the cell-based assay, respectively.
Keywords: Bupleurum chinense; Apiaceae; NF-κB; saponin; polyacetylene; lysophosphatidylcholine